Cetaceans Sightings During Research Cruises in Three Remote Atlantic British Overseas Territories - Martin, Stephanie M.; Soeffker, Marta; Schofield, Andy; Hobbs, Rhys; Glass, Trevor; Morley, Simon A. (Frontiers in Marine Science, 2021)
Marine mammal sightings were recorded during research cruises to three remote, mid-ocean British Overseas Territories in the South Atlantic and Southern Ocean. In March to April 2018 and 2019, the Exclusive Economic Zones (EEZs) of tropical St Helena and temperate Tristan da Cunha were surveyed. The sub-polar waters of South Georgia and the South Sandwich Islands (SGSSI) were surveyed in February to March 2019. At St Helena in 2018, five species were recorded during 11 sightings, and in 2019, four species, with one additional unidentified species, during seven sightings. Most of these sightings were of dolphin species, which are known to be resident around the Island and seamounts. In Tristan da Cunha in 2018, a total of five identified and one unidentified species were recorded during six sightings, half of which were associated with the Islands or seamounts. In 2019, due to rough weather, no sightings were recorded in the Tristan da Cunha waters. Around SGSSI, 162 sightings of 236 cetaceans were made in 2019, mostly of baleen whales, with seven species identified with certainty. Sightings around the southern South Sandwich Islands included beaked whales and large dolphins, whereas baleen whales dominated in the northern South Sandwich Islands. These results provide new data for rarely surveyed regions, helping to build a spatial picture of important areas for marine mammals, which will help inform marine spatial protection strategies.